Project-based learning in English language classes in elementary schools - Buhrym, Alina (Univerzita Pardubice, 2025)
This thesis focuses on the usage of project-based learning in English language classes that are held in elementary schools. The theoretical part of the study deals with main characteristics of project-based learning and its integration into English classes. The thesis also examines how key competences outlined in Framework Educational Programme for Basic Education and communicative competences mentioned in the Common European Framework of Reference for Languages are developed with the help of project-based learning. The practical part focuses on the example of a project that meets the criteria outlined in the theoretical part.
Projektová výuka v hodinách anglického jazyka na ZŠ
Keywords: projektové učení; mladší školní věk; klíčové kompetence; komunikační kompetence; project-based learning; early school age; key competences; communicative competences